2012
DOI: 10.2478/v10048-012-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of Replica Technique and SEM in Accuracy Measurement of Ceramic Crowns

Abstract: The paper presents a comparative study of the measuring values of the marginal gap related to the ceramic crowns made by dental CAD/CAM system using the replica technique and SEM. The study was conducted using three experimental groups, which consisted of ceramic crowns manufactured by the Cerec CAD/CAM system. The scanning procedure was carried out using three specialized dental 3D digitization systems from the Cerec family -two types of extraoral optical scanning systems and an intraoral optical scanner. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…A number of studies have evaluated the accuracy of crowns and fixed dental prosthesis in vivo as well as in vitro . This technique offers the advantage that neither restoration nor abutment are destroyed during the assessment 1819…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have evaluated the accuracy of crowns and fixed dental prosthesis in vivo as well as in vitro . This technique offers the advantage that neither restoration nor abutment are destroyed during the assessment 1819…”
Section: Introductionmentioning
confidence: 99%
“…Trifkovic et al; evaluated the application of electron microscope and replica technique in marginal and internal gap measurements, they found that electron microscope is reliable regarding marginal gap evaluation. The values of marginal fits in ceramic crowns evaluated by the replica technique were statistically significantly lower compared to the values obtained by Electron Microscope 35 Some studies evaluated effect of the crown preparation margin and die type on the marginal accuracy of fiber-reinforced composite crowns. They compared the chamfer and shoulder finish line on stone and epoxy dies.…”
Section: Discussionmentioning
confidence: 81%
“…Samples cut from 15 mm plate were austenitised at 1250 °C with holding time of 3 minutes. The first group of Technical Gazette 23, 3(2016), 761-767 [23,24], and the space orientation of cleavage facets was determined with electron backscatter diffraction (EBSD) method [25].…”
Section: Experimental Workmentioning
confidence: 99%